A new species of Toccolosida, a Pyralinae from the Western Ghats, India (Lepidoptera, Pyralidae) and the revised status of Lixa as a synonym - Singh, Navneet; Kirti, Jagbir Singh; Ranjan, Rahul; Chandra, Kailash (Zootaxa, 2020)
A new species, Toccolosida ganeshgudiensis N. Singh, Kirti & Ranjan, sp. nov. is described from the Western Ghats of Karnataka, India, the furthest southern known distribution for the genus in India. Additionally, Lixa Walker, 1866 is synonymised with Toccolosida Walker, 1863 and L. productalis Walker is newly combined as Toccolosida productalis (Walker), comb. nov. An updated checklist and a taxonomic key to the known species of Toccolosida are also provided.